Moderating Role of CSR Disclosure on the Relationship Between Financial Constraints, Leverage, and Tax Aggressiveness - Putu Dhira Pratiwimba; Damayanthi, I Gst Ayu Eka (E-Jurnal Akuntansi, 2025)
Tax aggressiveness leads to suboptimal tax revenues and has negative implications for the country's overall economic well-being. This study explores the moderating role of corporate social responsibility (CSR) disclosure in examining the effects of financial constraints and leverage on tax aggressiveness. The research employs a purposive sampling method to select a sample of 82 mining companies and utilizes Eviews 13 for analysis through moderated regression techniques. The findings indicate that leverage is positively associated with tax aggressiveness, whereas financial constraints do not significantly impact tax aggressiveness. Furthermore, CSR disclosure mitigates the positive effect of leverage on tax aggressiveness but has no moderating impact on the relationship between financial constraints and tax aggressiveness. Theoretically, this study reinforces three distinct theories related to the variables examined. Practically, the research serves as a valuable resource for future studies and provides insights for company management and policymakers in the formulation of effective tax policies.